Code of practice for the selection, installation and maintenance of electrical apparatus for use in potentially explosive atmospheres Part 6. Installation and maintenance requirements for electrical apparatus (BSI, 1978)
Protected electrical equipment, Electrical equipment, Explosive atmospheres, Selection, Installation, Inspection, Marking, Electric motors, Type e protected electrical equipment